Student Perceptions of the Application of Social-Effective Strategies to the Speaking Confidence of 8 Year Students - Nurmayanti, Wa Ode; Korompot, Chairil Anwar; Sakkir, Geminastiti (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This research aimed to find out students’ perception of the application of socio-affective strategies on speaking confidence, factors affecting speaking confidence, the difficulties and convenience in increasing students’ speaking confidence, and how they solve problems related to speaking confidence. This research applied a descriptive qualitative method. The data collection in this research was conducted by interviewing seven students at SMPN 1 Sampolawa as the participants. The results of this study show that there are several pluses of the socio-affective strategies on speaking confidence these include friends who have a positive effect in helping to increase self-confidence, way of thinking, and participating in activities that can increase self-confidence. As for the drawbacks, this study found that when students always think negatively, it is difficult for them to control nervousness when speaking. It can be concluded that psychological factors influence students to increase confidence their in class.